1965
DOI: 10.1037/h0082888
|View full text |Cite
|
Sign up to set email alerts
|

Phase difference function in binocular flicker.

Abstract: Two experiments were carried out to determine the functional relation between the critical flicker frequency (CFF) of two identical intermittent targets, binocularly superimposed, and the phase difference between the targets. Binocular CFF is a monotonic decreasing function of phase difference, positively accelerated for phase differences between 0° and 180", and negatively accelerated for phase differences between 360° and 180°. It is postulated that the results can be accounted for by assuming the existence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1966
1966
1973
1973

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…1l)5~a. b. c. d: Baker & Batt, 1951: Foley & Stager, 1965: Ireland, 1950Kinsbourne & Coughlin, 1969: Perrin, 1954Thomas, 1954Thomas, , 1955Thomas, , 1956. Moreover, the differences in CFF between these two conditions, although not of the magnitude originally anticipated by Sherrington, are larger.…”
Section: Flicker Fusion Thresholdmentioning
confidence: 86%
“…1l)5~a. b. c. d: Baker & Batt, 1951: Foley & Stager, 1965: Ireland, 1950Kinsbourne & Coughlin, 1969: Perrin, 1954Thomas, 1954Thomas, , 1955Thomas, , 1956. Moreover, the differences in CFF between these two conditions, although not of the magnitude originally anticipated by Sherrington, are larger.…”
Section: Flicker Fusion Thresholdmentioning
confidence: 86%
“…He concluded that the "sensual reactions" of the "right and left corresponding retina-cerebral points, retain individually as regards time relations even when completely confluent by reference to visual space." In antiphase stimulation a decrement of CFF of no more than about 9% of inphase stimulation has since been confirmed repeatedly (Ireland, 1950;Baker & Bott, 1951;Perrin, 1954;Foley & Stager, 1965;Kinsbourne & Coughlin, 1969).…”
Section: Resultsmentioning
confidence: 95%
“…There is also evidence that the phase-difference function is asymrnetrical. Foley & Stager (1965) reported two experiments in which each pulse to the left eye was made to lag behind the corresponding pulse to the right eye in 45-deg steps, ranging from 0 to 180 deg in one experiment and from 180…”
Section: On the Asymmetry Of The Phase-difference Function In Binoculmentioning
confidence: 99%